Manual de procedimientos para la fabrica de harina de sangue del camal Frigorifico Municipal Riobamba. - Changoluisa Cayo, Nelly Margoth (2013)
The present work aims to develop the procedure manual for the flour blood factory in the “Camal Frigorífico Municipal Riobamba” (Riobamba Municipal Slaughterhouse, in English) In order to get a procedure manual, some field work was carried out; we applied the data collection instruments (survey and observation, etc.) to the population under study. The survey was applied to factory workers in order to know their roles and activities. Observation, as a research technique allowed us to "see" and "hear" the facts and phenomena that were developed during the exploration period for the entire process of production and operation of the machinery used in obtaining byproducts. The Manual contains three procedures which are: Raw materials, production and finished product control, each one with their respective instructions and registration forms for both blood flour processing and the manufacture of sebum blocks.